Electrochemical performance of novel NGCO-LSCF composite cathode for intermediate temperature solid oxide fuel cells - Samreen A.; Galvez-Sanchez M.; Steinberger-Wilckens R.; Arifin N.A.; Saher S.; Ali S.; Qamar A. (Elsevier Ltd, 2023)
Cathode materials; Cathodes; Cerium compounds; Gadolinium compounds; Neodymium; Neodymium compounds; Composite cathode; Electrochemical performance; Good compatibility; Intermediate temperature solid oxide fuel cell; Oxygen-ion diffusion; Polarization resistances; Spectroscopic characterization; Triple phase boundary; Solid oxide fuel cells (SOFC)